Produção e caracterização de filmes de PHB/PEG/ALG-e/NPsAg e PHB/ZnO/Ag com aplicação bactericida - Silva, Mário Rodrigues Pereira da (2018)
In this work, films based on poly(3-hydroxybutyrate) containing polymeric additives, such as alginate and polyethylene glycol, silver nanoparticles or hierarchical ZnO/Ag hybrid nanostructures were prepared and tested as bactericidal agents. AgNPs/citrate were produced in aqueous suspension and added to polymeric gels by the phase exchange technique. Zinc oxide (ZnO) nanostructures were prepared by a precipitation method in the presence of thiourea and, subsequently, decorated with AgNPs by a simple photoreduction method. Citrate-stabilized silver nanoparticles present diameters around 20 nm and plasmon band centered at 410 nm, as shown by TEM and UV-vis-NIR spectroscopy. On the other hand, when the metal nanoparticles are prepared in situ on ZnO surface, the plasmon band position is significantly affected by the initial concentration of silver nitrate. According to MEV and XRD data, ZnO particles show a flower morphology with a wurtzite crystal structure. For the sample prepared with the highest concentration of AgNO3, an additional peak at 38.5° suggests that AgNPs have a FCC structure. The films containing PHB, PEG, ALG-e and AgNPs were characterized by MEV and correlated with the water-vapor permeability (WVP). The presence of PEG increases the quantity and distribution of pores or defects, which increases the WVP. Thermal analyzes (TGA) of this material demonstrated a decrease in the degradation temperature of the PHB films containing the polymer additives and AgNPs, suggesting a catalytic effect. PHB films with ZnO or ZnO/Ag were characterized by diffuse UV/vis reflectance spectroscopy, XRD, FTIR-ATR and SEM. The characterizations corroborate the presence of both PHB and ZnO, with oxide particles well-dispersed on the polymeric matrix. The PVA assay of these films presented a higher permeation for the films containing ZnO or ZnO/Ag due to the increase of pores or surface defects of these films. Finally, the bactericidal activity of the as-prepared films in this work was tested against various bacterial strains, including Staphylococcus aureus, Pseudomonas aeruginosa, Klebisiella pneumoniae, Escherichia coli and Staphylococcus epidermidis. Preliminary results for these assays indicated that bacterial growth was unviable on the surface of films containing AgNPs, ZnO or ZnO/Ag. The data obtained so far demonstrate the potential of PHB matrix films and their variations for using as bio-curatives.